PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT EFARINA ETAHAM BERASTAGI - Nababan, Donal; Ginting, Isa Harpika; Sinaga, Janno (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
A preliminary study by conducting interviews with inpatients turned out that the patients were dissatisfied with going to the hospital for treatment. Today's society tends to demand better, friendlier and higher quality public services. The aim of this research is to analyze the influence of health service quality (physical evidence, reliability, responsiveness, assurance, empathy) on the satisfaction of inpatients at Efarina Etaham Berastagi Hospital. This research is a survey research with explanatory research type to explain the influence of health service quality on patient satisfaction for inpatient treatment at Efarina Etaham Berastagi Hospital in 2023. The population is all 74 patients hospitalized at Efarina Etaham Hospital during June-July 2023. Samples were taken from the entire population (total sampling). The research results showed that the majority of respondents were in the early adulthood age group, namely 61 people (82.5%). The majority of respondents were female, namely 69 people (93.2%). Respondents had moderate education, namely 37 people (50.0%). The results of statistical tests show that there is an influence of reliability, responsiveness, assurance and empathy on inpatient satisfaction. Doctors need to be punctual, nurses can provide help quickly, and provide the facilities that patients need. Keywords: Quality of service, patient satisfaction, inpatient care